2016
DOI: 10.1113/jp271593
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neuronal chloride homeostasis by neuromodulators

Abstract: KCC2 is the central regulator of neuronal Cl− homeostasis, and is critical for enabling strong hyperpolarizing synaptic inhibition in the mature brain. KCC2 hypofunction results in decreased inhibition and increased network hyperexcitability that underlies numerous disease states including epilepsy, neuropathic pain and neuropsychiatric disorders. The current holy grail of KCC2 biology is to identify how we can rescue KCC2 hypofunction in order to restore physiological levels of synaptic inhibition and neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 88 publications
4
38
0
Order By: Relevance
“…It was also abolished via blockade of metabotropic KAR signalling with GDP-β-S, suggesting that G-proteins are necessary for this process, and was also shown to be independent of zinc release at MF-CA3 terminals. This finding is in line with a growing body of literature suggesting that KCC2 activity can be regulated by a number of different receptors that signal via G-proteins, including mGluRs and mZnRs (Banke and Gegelashvili, 2008, Chorin et al 2011, Gilad et al 2015, Mahadevan and Woodin, 2016. KARs, similar to mGluRs and mZnRs, activate a G-protein signalling pathway that increases PKC activity (Melyan et al 2002, Lerma andMarques, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It was also abolished via blockade of metabotropic KAR signalling with GDP-β-S, suggesting that G-proteins are necessary for this process, and was also shown to be independent of zinc release at MF-CA3 terminals. This finding is in line with a growing body of literature suggesting that KCC2 activity can be regulated by a number of different receptors that signal via G-proteins, including mGluRs and mZnRs (Banke and Gegelashvili, 2008, Chorin et al 2011, Gilad et al 2015, Mahadevan and Woodin, 2016. KARs, similar to mGluRs and mZnRs, activate a G-protein signalling pathway that increases PKC activity (Melyan et al 2002, Lerma andMarques, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…The metabotropic signalling mode, which we have shown regulates E GABA and is dependent on KCC2 transporter activity, places KARs on a growing list of proteins that are able to regulate KCC2 via G‐protein signalling (Banke and Gegelashvili, , Chorin et al . , Mahadevan and Woodin, ). Two previous studies have reported an increase in transporter activity and expression of KCC2 upon KA application (Khirug et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, Ca 2+ influx through postsynaptic NMDA receptors or during prolonged postsynaptic firing 6 rapidly reduces KCC2 membrane expression and function through protein phosphatase 1-dependent dephosphorylation of its Ser940 residue and protein cleavage by the calcium-activated protease calpain 7,8,9 . Conversely, chloride influx through GABAA receptors stabilizes KCC2 at the plasma membrane via chloride-mediated inhibition of the serine/threonine WNK1 kinase and its downstream effectors SPAK/OSR1, which phosphorylate KCC2 on Thr906 and Thr1007 residues 10,11,12 . Finally, KCC2 expression is also regulated by several neuromodulators acting on G-protein couples receptors 13 as well as neurotrophins such as BDNF acting via TrkB signaling 14 .…”
Section: Introductionmentioning
confidence: 99%